Job Satisfaction among Employees of a Private Catholic Education Institution: A Baseline Study - Lacorte, Arianne; Quemuel, Xevious Paulive (JPAIR Multidisciplinary Research, 2024)
This study investigates job satisfaction among employees at San Sebastian College-Recoletos, a private Catholic education institution in the Philippines. Maslow’s hierarchy of needs was used to understand employee satisfaction. The research design incorporates a descriptive-comparative methodology to explore the relationships between ages, gender, years of service, salary, campus, classification, and overall job satisfaction. A self-administered survey is the data collection instrument with 80 participants from different employee classifications. Statistical analyses such as mean and Analysis of Variance examine differences in job satisfaction levels. Overall, employees reported that they are satisfied and that safety and security needs are the most confident among other needs. Meanwhile, the overall satisfaction of the employees significantly differs when they are grouped according to age. An action plan has been proposed based on the study findings. Recommendations for future research include longitudinal studies, qualitative investigations, exploration of alternative job satisfaction models, and a focus on specific areas for improvement based on employee needs.